Possible Missing Sources of Atmospheric Glyoxal Part II: Oxidation of Toluene Derived from the Primary Production of Marine Microorganisms - Renee T. Williams; Annika Caspers-Brown; Jennifer Michaud; Natalie Stevens; Michael Meehan; Camille M. Sultana; Christopher Lee; Francesca Malfatti; Yanyan Zhou; Farooq Azam; Kimberly A. Prather; Pieter Dorrestein; et al. (Metabolites)
Background: Glyoxal has been implicated as a significant contributor to the formation of secondary organic aerosols, which play a key role in our ability to estimate the impact of aerosols on climate. Elevated concentrations of glyoxal over open ocean waters suggest that there exists an additional source, different from urban and forest environments, which has yet to be identified. Methods: Based on mass spectrometric analyses of nascent sea spray aerosols (SSAs) and gas-phase molecules generated during the course of a controlled algal bloom, the work herein suggests that marine microorganisms are capable of excreting toluene in response to environmental stimuli. Additional culture flask experiments demonstrated that pathogenic attack could also serve as a trigger for toluene formation. Using solid-phase microextraction methods, the comparison of samples collected up-channel and over the breaking wave suggests it was transferred across the air–water interface primarily through SSA formation. Results: The presence and then absence of phenylacetic acid in the SSA days prior to the appearance of toluene support previous reports that proposed toluene is produced as a metabolite of phenylalanine through the Shikimate pathway. As a result, once in the atmosphere, toluene is susceptible to oxidation and subsequent degradation into glyoxal. Conclusions: This work adds to a minimal collection of literature that addresses the primary production of aromatic hydrocarbons from marine microorganisms and provides a potential missing source of glyoxal that should be considered when accounting for its origins in remote ocean regions.